Up-conversion of Er3＋/yb3＋ co-doped transparent glass-ceramics containing Ba2LaF7 nanocrystals - 胡金民 周大成 王荣飞 陈明厚 焦清 余雪 邱建备 (Journal of rare earths, 2013)
The up-conversion of Er3＋/yb3＋ co-doped transparent glass-ceramics 50SiO2-10A1F3-5TiO2-30BaF2-4LaF3-0.5ErF3-0.5YbF3 containing Ba2LaF7 nanocrystals under the changing of heat treatment temperature and time were investigated. The Ba2LaF7 nanocrystals precipitated from the glass matrix was confirmed by X-ray diffraction （XRD）. The structural investigation carried out by XRD and trans- mission electron microscopy （TEM） evidenced the formation of cubic Ba2LaF7 nanocrystals with crystal size of about 14 nm. Comparing with the samples before heat treatment, the high efficiency up-conversion emission of Er3＋/Yb3＋ co-doped samples was observed in the glass-ceramics under 980 nm laser diode excitation. The increase in red emission intensity bands was stronger than the green bands when the crystal size increased. The mechanism for the up-conversion process in the glass-ceramics and the reasons for the increase of Er3＋/yb3＋ co-doped up-conversion intensity after heat treatment were discussed.